2020
DOI: 10.1111/bju.14971
|View full text |Cite
|
Sign up to set email alerts
|

Information on surgical treatment of benign prostatic hyperplasia on YouTube is highly biased and misleading

Abstract: Objectives To assess the quality of videos on the surgical treatment of lower urinary tract symptoms associated with benign prostatic hyperplasia (LUTS/BPH) available on YouTube, given that such video‐sharing platforms are frequently used as sources of patient information and the therapeutic landscape of LUTS/BPH has evolved substantially during recent years. Materials and Methods A systematic search for videos on YouTube addressing treatment options for LUTS/BPH was performed in May 2019. Measures assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 15 publications
(24 reference statements)
7
36
0
3
Order By: Relevance
“…Prior work on written online information showed significant variability in the quality of medical recommendations for stone formers [22]. More recently, several studies have reported deficiencies in online video quality across a variety of urological conditions [17–19,23,24]. This is an area deserving of greater attention, as interest in kidney stone disease on YouTube has been steadily rising: worldwide searches for ‘kidney stones’ on YouTube have doubled since 2015 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work on written online information showed significant variability in the quality of medical recommendations for stone formers [22]. More recently, several studies have reported deficiencies in online video quality across a variety of urological conditions [17–19,23,24]. This is an area deserving of greater attention, as interest in kidney stone disease on YouTube has been steadily rising: worldwide searches for ‘kidney stones’ on YouTube have doubled since 2015 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Online information about urological conditions shared through Web 2.0, which refers to websites with user‐generated content and includes social media and online video‐sharing platforms, may have increased deficiencies compared to other sources of consumer information [16,17]. Several recent studies have also specifically focussed on the wide variability in quality of information on benign and non‐benign urological diseases available on YouTube, the leading online video sharing platform and one of the earliest Web 2.0 platforms [17–19].…”
Section: Introductionmentioning
confidence: 99%
“…(28) La glicina causa aumento de los niveles de amonio no obstante se necesitan aumentos de 10-15 veces para causar encefalopatía. (29) El sorbitol se metaboliza en glucosa, fructuosa y lactato, produciendo un efecto osmótico similar e inferior al manitol y actualmente se considera la solución con menos efectos adversos. (30) Nosotros no encontramos ningún caso de hiponatremia dilucional, comparado con un 6.46% en una muestra de 21 resecciones, estudiadas por Arbej JP, et al (6) La fistula vesico-cutánea es la mayor y más grave complicación que puede ocurrir en el sitio quirúrgico.…”
Section: Launclassified
“…This may lead to increase dissemination of misinformation. The previous studies of the authors on this subject have also emphasized that this problem is not only in the surgical treatment of urinary stones but also in other urological conditions [3].…”
mentioning
confidence: 94%